PERANCANGAN SISTEM INFORMASI GEOGRAFIS SEBARAN TANAMAN PANGAN BERBASIS SPASIAL DAN MULTI TIER MENGGUNAKAN MAP SERVER - Kristoko Dwi Hartomo; Andeka Rocky Tanaamah; Gogo Krisatyo (Universitas Kristen Duta Wacana, 2014)
The province of Central Java is one of the important national crop producers, therefore its productivity of rice and other crops are always at the highest priority (Central Java in Numbers, 2009). To achieve this, all efforts must be arranged systematically and correctly, and one of the efforts is making an accurate inventory of crop fields and production centres which distributed across the province, to provide a good mapping of produce. The research designs a system which capable to create spatially based crops distribution maps, which in turn helps the planning, operation, monitoring, and evaluation of crop production by departments in charge. The mapping is presented using the multi-tier architecture. The distribution map will include crops produce capacity for each year over the whole province. Implementation results are the system performs successfully, and the process time is reasonable, therefore it is applicable.